2020
DOI: 10.1055/s-0040-1714209
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Randomized Controlled Trial of Diabetes Group Prenatal Care

Abstract: Objective This study aimed to determine the feasibility and effectiveness of Diabetes Group Prenatal Care to increase patient engagement in diabetes self-care activities. Study Design A pilot randomized controlled trial was conducted at two sites. Inclusion criteria were English or Spanish speaking, type 2 or gestational diabetes, 22 to 34 weeks of gestational age at first study visit, ability to attend group care at specified times, and willingness to be randomized. Exclusion criteria included typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Finally, 18 articles, encompassing data from 20 studies, were included in evidence synthesis. 6 , 7 , 9 , 36 , 37 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51
Figure 1 Study selection process
…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 18 articles, encompassing data from 20 studies, were included in evidence synthesis. 6 , 7 , 9 , 36 , 37 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51
Figure 1 Study selection process
…”
Section: Resultsmentioning
confidence: 99%
“…Education regarding GDM control, healthy eating, and physical activity are practical interventions that improve self-care and empower women with diabetes [ 54 , 55 ]. Centering Pregnancy group prenatal care model, has demonstrated encouraging outcomes in improving nutrition and lifestyle among women with diabetes [ 32 ]. However, existing studies on the Centering Pregnancy model have predominantly focused on healthy pregnant women, and there is a lack of qualitative or mixed-methods research specifically investigating its effectiveness in pregnant women with diabetes [ 48 , 56 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Measuring the level of satisfaction with antenatal care using the Visual Analog Scale (VAS) involves a graded line ruler that is 10 centimeters long. The woman is required to indicate her level of satisfaction on this graded line, with zero representing dissatisfaction and 10 representing the highest level of satisfaction [ 32 ].…”
Section: Study Phasesmentioning
confidence: 99%
“…A recent pilot intervention for pregnant women with diabetes saw an unprecedented adherence rate of 93%, along with successful recruitment; authors noted that study sites had a strong, pre-established commitment to diabetes prevention that may have contributed to the program’s success ( Carter et al, 2022 ). More importantly, they concluded that buy-in of study site providers and staff were key drivers to successful recruitment outcomes.…”
Section: Discussionmentioning
confidence: 99%